2015
DOI: 10.1007/s11060-015-1813-2
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation and vertebral augmentation for palliation of painful spinal metastases

Abstract: Radiofrequency ablation (RFA) and vertebral augmentation is an emerging combination therapy for painful osseous metastases that cannot be or are incompletely palliated with radiation therapy. Herein, we report our experience performing RFA and vertebral augmentation of spinal metastases for pain palliation. Institutional review board approval was obtained to retrospectively review our tumor ablation database for all patients who underwent RFA of osseous metastases between April 2012 and July 2014. Patient demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
86
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 24 publications
2
86
0
1
Order By: Relevance
“…The pathophysiology of pain relief caused by RFA is unclear. One explanation is that it reduces pain by destroying nociceptors as well as reducing the tumor burden [40]. Gevargez, et al [41] showed that 41 patients treated with RFA for vertebral metastases experienced a significant reduction in VAS scores within six weeks (p = .001) and continued to be significant at six months (p = 0.002).…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathophysiology of pain relief caused by RFA is unclear. One explanation is that it reduces pain by destroying nociceptors as well as reducing the tumor burden [40]. Gevargez, et al [41] showed that 41 patients treated with RFA for vertebral metastases experienced a significant reduction in VAS scores within six weeks (p = .001) and continued to be significant at six months (p = 0.002).…”
Section: Reviewmentioning
confidence: 99%
“…Combining RFA and vertebroplasty provides a way to decrease tumor burden and retain or augment the supportive structure of the vertebral body. Wallace, et al [40] performed 72 RFA treatments with subsequent vertebroplasty in patients with spinal tumors. Patients treated with this combination of techniques experienced a significant decrease in VAS pain scores at one week and four weeks (median 3.25, 2.75, respectively; p < .0001).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 The tandem procedure can be performed in an outpatient setting with the patient under conscious sedation, requires minimal recovery, and does not hinder or delay adjuvant therapies such as radiation or systemic chemotherapy. Multiple case series have shown decreased pain scores after RFA and vertebral augmentation of spinal metastases, [11][12][13][14][15] but evidence that percutaneous therapy achieves local tumor control is limited to case reports and small case series without internal controls. 13,14 The purpose of this study was to retrospectively evaluate the rate of radiographic local control of spinal metastases treated with combination RFA and vertebral augmentation at a National Cancer Institute-Designated Cancer Center.…”
mentioning
confidence: 99%
“…
To the Editor, I read with great interest the article by Wallace and collaborators focusing on the combination of radiofrequency ablation (RFA) and vertebral augmentation for palliation of painful spinal metastases [1]. In a retrospective approach the authors reviewed a group of patients who underwent RFA for vertebral metastases in a period spanning almost 2 years.
…”
mentioning
confidence: 99%